2016
DOI: 10.1159/000448899
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Infarction and Factors Associated with Delayed Presentation and Misdiagnosis

Abstract: Background and Purpose: The diagnosis of cerebellar infarction (CBI) is often challenging due to non-specific or subtle presenting symptoms and signs. We aimed to determine whether a common syndromic cluster of symptoms, signs or vascular risk factors were associated with delayed presentation or misdiagnosis to an Emergency Department (ED). The degree of misdiagnosis between ED and neurology physicians and the influence of delayed presentation or misdiagnosis on outcome were also investigated. Methods: A prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…Our finding that PCS was disproportionately represented in misdiagnosed patients is consistent with the literature [10,11]. It also offers explanation why non-specific symptoms such as nausea/vomiting and dizziness as opposed to motor findings were more common in those misdiagnosed [5].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our finding that PCS was disproportionately represented in misdiagnosed patients is consistent with the literature [10,11]. It also offers explanation why non-specific symptoms such as nausea/vomiting and dizziness as opposed to motor findings were more common in those misdiagnosed [5].…”
Section: Discussionsupporting
confidence: 90%
“…Studies have reported that 2-26% of acute stroke presentations are misdiagnosed in the emergency department (ED) [5,[7][8][9][10]. Factors contributing to stroke misdiagnosis include non-specific or atypical symptoms [5,10], such as those associated with posterior circulation stroke (PCS) [8,10,11], decreased level of consciousness [9], younger patient age [8,9,12], lower cerebrovascular disease profile [8], and transient ischemic attack (TIA) [5].…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicate that NIHSS scoring is insensitive and misleading if it is used to guide decision‐making for posterior circulation infarction. It is not uncommon for patients with acute vestibular symptoms due to stroke to be either initially misdiagnosed with peripheral vestibular disease or have a delay in definitive diagnosis (Calic, Cappelen‐Smith, Anderson, Xuan, & Cordato, 2016). Moreover, DWI is associated with false negative results when performed very early, especially for posterior circulation infarction (Zuo et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It is postulated in these cases, that the lesions affected multisensory vestibular cortical networks involved in perceptive function, such as the thalamus, temporoparietal cortex, and peninsula adjacent to the inferior frontal gyrus (Dieterich & Brandt, 2008; Von Brevern, Süβmilch, & Zeise, 2014). It is not uncommon for patients with acute vestibular symptoms due to stroke to be either initially misdiagnosed with peripheral vestibular disease or have a delay in definitive diagnosis (Calic, Cappelen-Smith, Anderson, Xuan, & Cordato, 2016). Moreover, DWI is associated with false negative results when performed very early, especially for posterior circulation infarction (Zuo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of posterior circulation strokes is often missed or delayed . Between 28 and 59% of cerebellar strokes are initially misdiagnosed . In one study of 465 stroke patients, those with posterior strokes were 2.5 times more likely to be missed compared to anterior circulation strokes (38% vs. 16%) …”
Section: Discussion/observationsmentioning
confidence: 99%